2021
DOI: 10.3389/fpsyt.2021.694610
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Self-Guided Virtual-Reality Exposure Therapy for Public-Speaking Anxiety

Abstract: Objectives: Self-guided virtual-reality exposure therapy (VRET) is a psychological intervention that enables a person to increase their own exposure to perceived threat. Public-speaking anxiety (PSA) is an anxiety-provoking social situation that is characterized by fear of negative evaluation from an audience. This pilot study aimed to determine whether self-guided VRET (1) increases exposure to PSA-specific virtual social threats, and (2) reduces anxiety, arousal, heartrate and PSA over repeated exposure.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 81 publications
2
25
0
Order By: Relevance
“…VRE is currently used for the assessment and treatment of anxiety and related disorders, such as obsessive-compulsive disorders and posttraumatic stress disorders [ 9 , 13 ], as well as a diagnostic tool for paranoid ideations [ 14 ]. Studies show promising results for the treatment of social anxiety disorders and fear of public speaking [ 15 , 16 ] by including virtual humans that may be controlled by a therapist [ 17 ]. A comparable effectiveness of VRE in the treatment of anxiety disorders compared to in vivo treatment has been successfully identified in the broad spectrum of anxiety-related disorders [ 18 , 19 ] and specific phobias [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…VRE is currently used for the assessment and treatment of anxiety and related disorders, such as obsessive-compulsive disorders and posttraumatic stress disorders [ 9 , 13 ], as well as a diagnostic tool for paranoid ideations [ 14 ]. Studies show promising results for the treatment of social anxiety disorders and fear of public speaking [ 15 , 16 ] by including virtual humans that may be controlled by a therapist [ 17 ]. A comparable effectiveness of VRE in the treatment of anxiety disorders compared to in vivo treatment has been successfully identified in the broad spectrum of anxiety-related disorders [ 18 , 19 ] and specific phobias [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the PRPSA questionnaire showed that in both groups, the mean scores of speaking anxiety decreased, and this reduction was statistically significant in both groups. Premkumar et al, 16 by examining the effectiveness of VR therapy on public‐speaking anxiety in students, concluded that VR could reduce the reduction in heart rate and self‐reported anxiety and arousal in students. They believed increased self‐exposure to virtual social threats from self‐guided virtual‐reality exposure therapy alleviates anxiety and shows immediate decreases in subjective and physiological arousal during the application.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, participants with greater control during a computerized exposure task were able to approach closer towards a spider (Healey et al, 2017). Perceptual control theory suggests that exposure is more effective when clients have increased control over the process, for example in selfguided virtual reality exposure therapy (Healey et al, 2017;Premkumar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%